2019
DOI: 10.1176/appi.ajp.2019.18070825
|View full text |Cite
|
Sign up to set email alerts
|

Association of Choroid Plexus Enlargement With Cognitive, Inflammatory, and Structural Phenotypes Across the Psychosis Spectrum

Abstract: The choroid plexus is an important physiological barrier and produces CSF and neurotrophic, angiogenic, and inflammatory factors involved in brain development. Choroid plexus abnormalities have been implicated in both schizophrenia and bipolar disorder. A previous choroid plexus transcriptomic analysis of schizophrenia identified an upregulation of immune and inflammatory genes that correlated with peripheral inflammatory markers. The purpose of this study was to examine choroid plexus volume in probands acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 37 publications
11
93
3
Order By: Relevance
“…The choroid plexus, located in brain ventricles, is responsible for production of cerebrospinal fluid (CSF) and its volume is related with pathogenesis of neurodegenerative diseases, such as the clearance of CSF proteins ( Tadayon et al, 2020 ). Larger choroid plexus volume is also related to smaller total gray matter and larger lateral ventricle volumes ( Lizano et al, 2019 ). Recently, there is a report that an increased volume of choroid plexus is associated with increased vascular burden ( Egorova et al, 2019 ), which could be related to an increase in cerebrovascular pulsatility.…”
Section: Discussionmentioning
confidence: 99%
“…The choroid plexus, located in brain ventricles, is responsible for production of cerebrospinal fluid (CSF) and its volume is related with pathogenesis of neurodegenerative diseases, such as the clearance of CSF proteins ( Tadayon et al, 2020 ). Larger choroid plexus volume is also related to smaller total gray matter and larger lateral ventricle volumes ( Lizano et al, 2019 ). Recently, there is a report that an increased volume of choroid plexus is associated with increased vascular burden ( Egorova et al, 2019 ), which could be related to an increase in cerebrovascular pulsatility.…”
Section: Discussionmentioning
confidence: 99%
“…↑ Expression of genes related to immune function and inflammation associated with the disease status [296] ↑ CP volume [297] Chorionic Stress ↓ 5HT2C, glucocorticoid receptor, cilia genes IFT88 expression ↑ 5HT2A, BDNF, TNFα, IL-1β expression [298] CP papilloma, but not between CP papilloma and CP carcinoma. These changes include villous hypertrophy and diffuse enlargement of the CP with normal histological appearance [278].…”
Section: Schizophreniamentioning
confidence: 99%
“…Increased CP volume and an associated upregulation of genes related to immune function in the CP has been observed in patients suffering from schizophrenia [296,297].…”
Section: Effect Of Schizophrenia and Chronic Stress On Cpmentioning
confidence: 99%
“…3 We also found that dysbiosis of the gut induced depressive-like behaviors by means of the microbiota/gut/ brain axis. 4,5 A recent trial showed that CP volume was significantly increased in psychosis probands, 6 suggesting involvement of the CP across the psychosis spectrum with a latent pathophysiological mechanism. However, function of the CP in neuropsychiatric disease remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%